Studies on the stereoselective synthesis of the C17 backbone of the Alternaria toxins using chiral sulfoxide methodology - Vleggaar, Robert (University of Pretoria, 2013)
Dissertation (MSc (Chemistry))--University of Pretoria, 2007.